Dystocia Due to a Dicephalic Monstrosity of a Conjoined Twins in a Sahel Breed Doe Goat - Ali, Rahmatu Ibrahim; Umar, Aisha Zagga; Peter, Innocent Damudu; Waziri, Mohammed Ahmed (Animal Reproduction Update, 2025)
A female Sahelian goat was presented to the State Veterinary Clinic in Damaturu, Yobe State, Nigeria, with a complaint of prolonged and exhaustive straining lasting nine hours. The doe had a history of assisted deliveries and was confirmed to be in a full-term pregnancy. Upon clinical examination, vaginal palpation revealed a fully dilated cervix with a malpresentation of fetal parts (hind limbs of one fetus and a lateral head deviation in the other). Fetal reflexes indicated live fetuses. A cesarean section was performed, resulting in the delivery of three male kids—one normal and a conjoined dicephalic monster.